2010
DOI: 10.1186/1471-2490-10-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of bone metabolism in prostate adenocarcinoma

Abstract: BackgroundOsteoporosis could be associated with the hormone therapy for metastatic prostate carcinoma (PCa) and with PCa per se. The objective of this review is to determine the incidence of bone loss and osteoporosis in patients with PCa who are or are not treated with hormone therapy (ADT).MethodsThe Medline, Embase, Cancerlit, and American Society of Clinical Oncology Abstract databases were searched for published studies on prostate cancer and bone metabolism. The outcomes assessed were: fracture, osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 44 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…This suggests that androgens play an important role in regulating vitamin D metabolism and therefore calcium metabolism. Studies have shown that antiandrogen therapy in men is associated with osteoporosis and risk of fracture (48). Consistent with a role for androgens in the control of vitamin D and calcium metabolism, Francis et al (49) found that serum 1,25(OH) 2 D levels and intestinal calcium absorption increased significantly after testosterone treatment in hypogonadal men.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that androgens play an important role in regulating vitamin D metabolism and therefore calcium metabolism. Studies have shown that antiandrogen therapy in men is associated with osteoporosis and risk of fracture (48). Consistent with a role for androgens in the control of vitamin D and calcium metabolism, Francis et al (49) found that serum 1,25(OH) 2 D levels and intestinal calcium absorption increased significantly after testosterone treatment in hypogonadal men.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer typically occurs at an age when serum testosterone levels are naturally decreasing in men. The initiation of ADT results in dramatic hypogonadism, which causes decreased bone mineral density (BMD) and muscle loss . Men receiving ADT have been shown to have a 5‐ to 10‐fold increased loss of BMD at multiple skeletal sites, with maximal loss occurring within the first year after ADT initiation .…”
Section: Introductionmentioning
confidence: 99%
“…Oral bisphosphonates are generally poorly absorbed and have gastrointestinal side effects, leading to low patient adherence with these drugs. 14 , 15 Due to lack of adherence, intravenous bisphosphonates are preferred to oral bisphosphonates in this patient population. Oral bisphosphonate use was not captured because the Medicare database does not collect details of oral therapy.…”
Section: Methodsmentioning
confidence: 99%